Phenotyping hypertrophic cardiomyopathy using cardiac diffusion magnetic resonance imaging: the relationship between microvascular dysfunction and microstructural changes. (25th October 2021) - Das, Arka; Kelly, Christopher; Teh, Irvin; Nguyen, Christopher; Brown, Louise A E; Chowdhary, Amrit; Jex, Nicholas; Thirunavukarasu, Sharmaine; Sharrack, Noor; Gorecka, Miroslawa; Swoboda, Peter P; Greenwood, John P; et al.
Abstract: Aims: Microvascular dysfunction in hypertrophic cardiomyopathy (HCM) is predictive of clinical decline, however underlying mechanisms remain unclear. Cardiac diffusion tensor imaging (cDTI) allows in vivo characterization of myocardial microstructure by quantifying mean diffusivity (MD), fractional anisotropy (FA) of diffusion, and secondary eigenvector angle (E2A). In this cardiac magnetic resonance (CMR) study, we examine associations between perfusion and cDTI parameters to understand the sequence of pathophysiology and the interrelation between vascular function and underlying microstructure. Methods and results: Twenty HCM patients underwent 3.0T CMR which included: spin-echo cDTI, adenosine stress and rest perfusion mapping, cine-imaging, and late gadolinium enhancement (LGE). Ten controls underwent cDTI. Myocardial perfusion reserve (MPR), MD, FA, E2A, and wall thickness were calculated per segment and further divided into subendocardial (inner 50%) and subepicardial (outer 50%) regions. Segments with wall thickness ≤11 mm, MPR ≥2.2, and no visual LGE were classified as 'normal'. Compared to controls, 'normal' HCM segments had increased MD (1.61 ± 0.09 vs. 1.46 ± 0.07 × 10 −3  mm 2 /s, P  = 0.02), increased E2A (60 ± 9° vs. 38 ± 12°, P  < 0.001), and decreased FA (0.29 ± 0.04 vs. 0.35 ± 0.02, P  = 0.002). Across all HCM segments, subendocardial regions had higher MD and lower MPR than subepicardial (MDendo 1.61 ± 0.08 × 10 −3  mm 2 /s vs. MDepi 1.56 ± 0.18 × 10 −3  mm 2 /s, P  = 0.003, MPRendo 1.85 ± 0.83, MPRepi 2.28 ± 0.87, P  < 0.0001). Conclusion: In HCM patients, even in segments with normal wall thickness, normal perfusion, and no scar, diffusion is more isotropic than in controls, suggesting the presence of underlying cardiomyocyte disarray. Increased E2A suggests the myocardial sheetlets adopt hypercontracted angulation in systole. Increased MD, most notably in the subendocardium, is suggestive of regional remodelling which may explain the reduced subendocardial blood flow.